Religious Commitment and Freedom - Kadadkavil, Thomas (Journal of Dharma, 1987)
The human soul IS ever thrilled by the prospects of freedom. When Rousseau wrote, in The Social Contract that "man is born free; and every- where he is in Chains," he became a champion of human freedom. A little over a century ago, communists came up with their version of the ideal of freedom, a freedom in the economic sphere. The Manifesto of the Communist Party declares: "here it becomes evident, that the bourgeosie is unfit any longer to be the ruling class in society, and to impose its conditions of existence upon society as an over-riding law. It is unfit to rule because it is incompetent to assure an existence to its slave within its slavery ... " "Let the ruling classes tremble at a communistic revolution. The proletarians have nothing to lose but their chains. They have a world to win."